Cognitive Behavioral and Mindfulness-Based Interventions for Smoking Cessation: a Review of the Recent Literature - Vinci, Christine (Curr Oncol Rep, 2020)
PURPOSE OF REVIEW: Cigarette smoking is the primary cause of cancer and is the leading preventable cause of morbidity and mortality. Cognitive behavioral therapy (CBT) is one of the most well-established and efficacious interventions for smoking cessation. The study of mindfulness-based interventions (MBIs) has increased exponentially in recent years, showing efficacy for smoking cessation as well. This review highlights research from the past 5 years examining CBT and MBIs for smoking cessation. RECENT FINDINGS: Both CBT and MBIs are efficacious for special populations (e.g., low SES; pregnant smokers) and have shown initial efficacy when delivered via mhealth/ehealth. CBT has shown efficacy when combined with another behavioral treatment (e.g., ACT). SUMMARY: Continued research is needed on CBT and MBIs that have high potential for scalability. Understanding whether they are beneficial for certain populations (e.g., cancer survivors), along with determining for whom CBT vs MBIs are most effective, is also needed.